The Relationships of Body Weight with Onset and Duration of Estrous in Kacang Goat - Hastono, Hastono; Bintang, IAK (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
The objectives of the study were to know relationships between body weight and onset of estrous and duration of estrous. Data of body weight, onset of estrous and duration of estrous resulted from 36 Kacang goats were subjected to simple correlation and regression analysis. Coefficient correlation and regression equation of body weight I (23.33 ± 2.24 kg) to onset of estrous (r = 0.50, Y =126.28 + 0.49 X), duration of estrous (r = 0.28, Y = 35.32 + 0.73 X), and of body weight II (27.92 ± 2.24 kg) to onset of estrous (r = 0.26, Y =37.42 + 0.44 X), duration of estrous (r = 0.73, Y =26.30 + 0.31 X). It be can concluded that body weight I closely affected to the onset of estrous while body weight II closely affected to the duration of estrous. (Animal Production 10(3): 147-150 (2008) Key Words: Goat, body weight, estrous, Kacang